COVID-19 pandemic and its impacts on the environment: A global perspective - Otolorin, Gbeminiyi R.; Oluwatobi, Akefe I.; Olufemi, Olaolu T.; Esonu, Daniel O.; Dunka, Hassana I.; Adanu, Williams A.; Danjuma, Friday A.; Abiayi, David C.; Adegoke, Victoria A.; Omoniwa, David O.; Oghenefega, Ovwighose N.; Mshelbwala, Philip P. (Narra J, 2022)
Many researchers worldwide have focused on the health impact of the coronavirus disease 2019 (COVID-19) pandemic without paying much emphasis to the environmental impacts associated with the pandemic. Evidence suggests that prior to the pandemic there was an alarming increase in environmental pollution due to rising industrialization, in particular in urban areas. Following the COVID-19 pandemic, satellite data over Asia and Europe showed a substantial decrease in air pollution, in particular nitrogen dioxide. However, the increase in industrial and household wastes may pose a significant challenge to  environmental management. The improper management of these wastes poses an unforeseen “knock-on” effect on human health and the environment. It is imperative to establish an effective and safe procedure, for handling and disposing of the consequential wastes accumulating during the pandemic. The  review aims to highlight both the beneficial and detrimental effects of COVID-19 pandemic on the natural environment and  to discuss the possible strategies to improve the quality of the global environment during the period of the pandemic and beyond.